Option on futures : - Summa, John F. (John Wiley & Son, Inc., 2002)
Learn How to Profit from Option Selling and Time-Value Decay . "John Summa and Jonathan Lubow make a special contribution to the trading literature with their book Options on Futures: New Trading Strategies. Among other notable features of the book, the authors present their favorite trading setups for S&P 500 and commodity futures options, an excellent chapter covering SPAN margin requirements, and actual trades and follow-up adjustments under far from ideal market conditions. The book drives home the point that options on futures should be part of any trader’s arsenal. The authors’ premium selling approach will come as an eye-opener for many options traders who remain confined to option buying strategies. If you want to learn how to trade options on futures, there is no better place to start. This outstanding book, coauthored by John Summa, who is one of the best options educators and traders in the business, provides a practical, hands-on explanation of how to trade options on futures. Options on Futures is full of trading nuances and key insights that make it uniquely effective. Highly recommended reading!"